CANTIK Economic Learning Model as a Stimulator of Students' Reactive Behavior - Cahyo Apri Setiaji; Anita Rinawati; Lusy Rahmawati; Nurshahira Ibrahim (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
The background to this research is the low level of active student participation in classroom learning. As a result, learning interaction is low and learning outcomes are suboptimal. This study aims to develop the CANTIK economics learning model to support the improvement of students' reactive behavior. Data collection methods used observation, interviews, and documentation and literature studies. The research instrument used interview guidelines and checklist observation sheets. Data analysis used comparison tests, multivariate T-tests, and N-Gain tests. Model development began with a preliminary study to identify learning needs and problems. Before being implemented, the CANTIK model design went through a validator test stage by model validators, material validators, and expert practitioner validators. The results of the validator test showed that the CANTIK model was declared very valid for use in the next stage. Next, the CANTIK model was subjected to limited trials, field trials, and dissemination. The test results showed that there was a significant increase in students' reactive behavior after receiving treatment using the CANTIK model. The reactive behavior of the very high category of the control group and the experimental group has a significant difference of 0.000 <0.005 or 34.4%. The reactive behavior of the high category of the control group and the experimental group has a significant difference of 0.000 <0.005 or 10.8%. Hasil Uji N-Gain menunjukkan bahwa N-Gain score is 0.89>0.7, meaning that the effectiveness of the CANTIK model. While the mean value of the N-Gain percent is 89%>76, meaning that the CANTIK model effectively improves the reactive behavior students.